"Efecto de tres productos orgánicos en el manejo de la PC (Pudrición de cogollo) de la palma Aceitera (Elais guineensis Jacq.)" - Intriago Andrade, Isidro Isidro (2012)
This research was developed at the plantation Energy & palma, located at Km 27 via San Lorenzo-Ibarra, parish Carondelet was developed between the months of May and November, 2010 with these geographic location temperature: 27.5 ° C, relative humidity: 85-97% precipitacion:2300 mm lightness: 89.27 kw m-2in the area north of Esmeraldas has been disease (Bud rot) PC which is decimating African Palm growing material guineensis. It is estimated that it was removed around 15000 has cultivation in this area and nationally around 30000 has since the appearance of this disease, there has been controlling the progress of PC, his or her agents or its possible controls, both natural and/or chemicals by which this research is put aiming general "to assess the effect of organic products in the management of Bole rot"(PC) in palm plantations in the North of Esmeraldas"; and, as specific: 1.) to determine the effect of TIMOREX GOLD, HUMAT - 7 PLUS, ALGAENZIM + XCALIBOR - K, absolute control in the evolution of the disturbance of the PC. (2) Carry out economic analysis of treatments applying the methodology of Perrin (1987) and whose hypothesis H0: the treatments evaluated no impact on the evolution of the disturbance of the PC.H1: